2022
DOI: 10.3390/cells11020205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms in Pentanucleotide Repeat Diseases

Abstract: The number of neurodegenerative diseases resulting from repeat expansion has increased extraordinarily in recent years. In several of these pathologies, the repeat can be transcribed in RNA from both DNA strands producing, at least, one toxic RNA repeat that causes neurodegeneration by a complex mechanism. Recently, seven diseases have been found caused by a novel intronic pentanucleotide repeat in distinct genes encoding proteins highly expressed in the cerebellum. These disorders are clinically heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 185 publications
(360 reference statements)
0
21
0
2
Order By: Relevance
“…IDRs are characterized by low amino acid complexity (LC), absence of hydrophobic residues, and enrichment in charged residues [ 147 ]. The regions with a low amino acid complexity (low-complexity domains, LCDs) may contain poly-glutamine and poly-alanine tracts and seem to favor the structuration of ribonucleoprotein complexes [ 148 , 149 , 150 ].…”
Section: Post-transcriptional Regulation Of Gene Expression In the Ne...mentioning
confidence: 99%
“…IDRs are characterized by low amino acid complexity (LC), absence of hydrophobic residues, and enrichment in charged residues [ 147 ]. The regions with a low amino acid complexity (low-complexity domains, LCDs) may contain poly-glutamine and poly-alanine tracts and seem to favor the structuration of ribonucleoprotein complexes [ 148 , 149 , 150 ].…”
Section: Post-transcriptional Regulation Of Gene Expression In the Ne...mentioning
confidence: 99%
“…Incorrect or abnormal phase separation of biological macromolecules is closely related to the occurrence of many types of diseases, such as cancer, neurodegenerative diseases, and infectious diseases [ 41 , 42 , 43 ]. The formation and regulation of aberrant biomolecular condensates is changing the way people think about coping with many diseases, including tumor genesis, diagnosis, and treatment.…”
Section: Mechanisms Of Phase Separation In Tumorigenesismentioning
confidence: 99%
“…Expansions of pyrimidine-rich CCTG, ATTCT and ATTTT/ATTTC repeats are associated with myotonic dystrophy type 2 (DM2) [27] , spinocerebellar ataxia type 10 (SCA10) [28] , and SCA37 and six subtypes of familial adult myoclonic epilepsy (FAME) [29] , respectively. An earlier chemical/enzymatic probing study showed the hairpin formation propensity of CCTG repeats [30] , and a subsequent NMR study revealed that CCTG repeats formed hairpin and dumbbell structures [31] .…”
Section: Introductionmentioning
confidence: 99%